(untitled) (Journal of Pharma Insights and Research, 2024)
The escalating global challenge of antimicrobial resistance, combined with increasing healthcare costs, demands a thorough understanding of pharmacoeconomic principles in antimicrobial use. The integration of pharmacoeconomics with antimicrobial stewardship has emerged as a crucial factor in promoting sustainable pharmacy practices. Recent evidence from the past decade demonstrates that well-structured antimicrobial stewardship programs achieve significant cost savings through reduced drug expenditure, decreased length of hospital stay, and improved clinical outcomes. Targeted interventions, including prospective audit with feedback and formulary restriction, consistently yield substantial returns on investment. The implementation of clinical decision support systems and rapid diagnostic technologies, despite requiring initial capital investment, has proven cost-effective in long-term healthcare settings. Both direct and indirect costs play vital roles in antimicrobial therapy decisions, encompassing resistance-related expenses and broader societal impact. Preventive strategies and appropriate antimicrobial selection significantly reduce healthcare-associated costs while maintaining therapeutic efficacy. This information provides healthcare administrators and clinical practitioners with essential information for developing economically sustainable antimicrobial use practices while ensuring optimal patient care. The economic value of implementing comprehensive antimicrobial stewardship programs extends beyond immediate cost savings to include long-term benefits in resistance prevention and resource optimization